Do cosmopolitismo ao “comumpolitismo” enquanto um novo ambiente para os direitos humanos na era do império - Hoffmam, Fernando (Universidade do Vale do Rio dos Sinos, 2018)
The This paper pretends to (re) understand the modern-European paradigm of Human Rights, as well as the European cosmopolitan(s) Project(s) until the contemporaneity, inserted in a new sovereignty paradigm, that in Michael Hardt and Antonio Negri work receives the name of “Empire”. In this way, it pretends to unveil the Human Rights current model, as well as the cosmopolitan Project from Kant to Höffe inserted at the “Imperial” context, and, specially, in the middle of a state of war that stands as a real exception state, instituted by the “Empire”. The “Empire” as a worldwide/global biopower, institutes a process of biopolitical control of the humanity – that itself does not consider human – as an expropriation and exclusion process of those who do not serve the capitalist system. However, from the theoretical reference of Antonio Negri and Michel Hard it is possible to identify a “biopolitical change” towards a biopolitical Project of and for life, anchored in the multitudinous “common” movements. In this plan, it is the central thesis of the present work to constitute the "common" as a constituent subject and as a new subject of and for human rights that are rethought as content of struggle and resistance through the "common crowd" against the “Empire". In this way, "comumpolitism" or "cosmopolitanism of the common" is proposed as a condition and possibility to construct a new "place" for human rights in the age of the "Empire", having in the "common" a new antagonistic and revolutionary political subject, against the "imperial" mechanisms of domination, exclusion and elimination.
Keywords: Biopolítica; Comum; Comumpolitismo; Direitos humanos; Império; Multidão; Biopolitics; Common; Comumpolitism; Human rights; Empire; Crowd; ACCNPQ::Ciências Sociais Aplicadas::Direito